Obstacles to participating in volunteer work among students of humanitarian faculties - Alsolami, Aref Awadhallah (Journal of Humanities & Social Sciences, 2022)
The current study aimed to identify the most important obstacles that limit the participation of King Saud University students in voluntary work. The most important of these obstacles are academic, economic, and social obstacles. The researcher used the sample social survey method, to find out the students’ opinions about these obstacles by applying the research questionnaire to a random sample of (103) students representing the humanities faculties of the university only. The study reached the following most important results: That (73.8%) of the sample members have the desire to participate in voluntary work, and (71.8%) of the sample members have previously participated in voluntary work. Also, there is agreement among university students on the academic obstacles that prevent their participation in the voluntary work. Volunteer work. There is also approval among university students on the economic obstacles that prevent their participation in volunteer work. There is also approval among university students on social obstacles that prevent their participation in volunteer work. Whereas the economic obstacles that prevent students from participating in volunteer work ranked first with an arithmetic average (3.76), secondly, social obstacles with an arithmetic average (3.73), and thirdly and finally academic obstacles with an arithmetic average (3.70) of all sample members. The study also showed that students who have a desire to participate in voluntary work agree more with academic obstacles that prevent their participation in voluntary work.